Status Perkawinan Gereja Yang Tidak Dicatatkan Di Kantor Catatan Sipil - Benny Haryono (Universitas Mahendradatta, 2020)
Marriage is an inner bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family (household) based on the Godhead of the Almighty. However, if marriage is not recorded, it can affect the couple's access to legal activities or moral and social aspects, such as allegedly committing adultery or so on, this has sociological consequences in the community, so that marital registration plays a role in the engineering of social interaction in society. This research uses normative juridical research type. This study uses a statutory approach and a conceptual approach. The legal material analysis technique used is normative analysis, a way of interpreting and discussing the results of research based on the notion of law, legal norms, legal theories and doctrines relating to marital status that are not recorded in the civil registry office. The result of this research is a marriage that is not registered at the Civil Registry Office, so the marriage is still considered valid. However, there are juridical consequences related to the marriage. And the impact on the church's marital status that is not recorded is that they cannot do legal actions and have no legal protection